Blockchain-based data-sharing acceptance among intelligence community - Muhamad, Wan Nurhidayat bin Wan (Cranfield University Defence and Security, 2024)
Data sharing among the intelligence community are critical to enable data analysis in supporting decision making hence preserving the security of the nation. However, sharing data between various parties is complicated due to the confidentiality and the risk of its exposure to unauthorised users and attackers. Hence, application of blockchain technology as a secure data sharing mechanism potentially safeguarding the data. However, the acceptance and readiness of the user to use this technology is questionable. This research aims to identify factors influencing user acceptance and to evaluate the acceptance level of blockchain-based data-sharing among the intelligence community in Malaysia by integrating Technology Acceptance Model 3 and Technology Readiness Index 2.0. This study applied an extensive literature review and empirical research using a survey questionnaire of data from 210 respondents from the intelligence communities. Descriptive and demographic data analysis using IBM SPSS software version 27 was used in this study. The acceptance model is analysed and verified using PLS-SEM method by using SmartPLS version 3.3.2. The results indicate that 10 out of 12 hypotheses is accepted and the acceptance is below moderate level. Hence, personality traits and feeling influenced the acceptance of the blockchain-based data-sharing system in the intelligence community. Overall, the result can assist the administration to manage the technology implementation process and to provides the system and architecture requirement in developing blockchain-based data sharing for the use of the intelligence community.
Keywords: Blockchain technology; data sharing; intelligence community; data security; decentralized systems; trust management; technology acceptance; technology readiness